Digital Empowerment Foundation's Chanderiyaan Project: linking the poor producers with the market using ICT. Issue 3 (23rd August 2018) - Singh, Ramendra; Modi, Pratik; Gupta, Vaibhav; Sur, Arindam
Abstract : Subject area: Non-governmental organization (NGO) intervention in poor communities using information and communication technology (ICT). Study level/applicability: BBA, MBA courses on marketing management, social entrepreneurship, rural marketing, marketing to bottom of pyramid. Case overview: In 2009, Digital Empowerment Foundation (DEF) along with Media Labs Asia and the Ministry of Information and Communication Technology (MICT) established the Chanderi Weavers ICT Resource Centre (CWIRC) as a self-sufficient community information resource center involved in skills' enhancement of weavers at Chanderi in Madhya Pradesh. The next three years of CWIRC resulted in an overall growth of the project with progress in the various domains of handloom industry through ICT-enabled development of weavers and weaving. The project not only aimed at the handloom industry revival and development, but also advanced in other sectors such as education, health and tourism. Osama Manzar, the DEF founder, is in a dilemma as to whether the local community of weavers in Chanderi would be able to continue with the sustainable ecosystem created in Chanderi. Is it the right time to exit Chanderi? Expected learning outcomes: Issues related to the market development at the bottom of the pyramid; managing local communities and building their capabilities for marketing; marketing strategies of community marketing efforts; and key success factors for ensuring successful completion of any developmental project. Supplementary materials: Teaching Notes are available for educators only. Please contact your library to gain login details or email support@emeraldinsight.com to request teaching notes. Subject code: CSS 8: Marketing.